Reductive dearomative arylcarboxylation of indoles with CO2 via visible-light photoredox catalysis - Wen-Jun Zhou (Nature Portfolio, 2020)
Catalytic reductive coupling of two electrophiles and one C = C bond is usually performed by two electron transfer metal catalysis. Herein, the authors show a visible light photoredox-catalyzed successive single electron transfer leading to dearomative arylcarboxylation of indoles with CO2 and generating indoline-3-carboxylic acids.